Tourism : principles, practices, philosophies - Goeldner, Charles R.; Ritchie, J.R. Brent (John Wiley and Sons, 2012)
This updated and revised Eleventh Edition of Tourism presents a comprehensive introduction to travel and tourism, while continuing the tested approach of successful previous editions. New and revised coverage, integrating the latest developments in the tourism industry.
Includes bibliographical references and index.
Keywords: Tourism